The Spread of Emerging Contaminants in the Soil-Groundwater System - (:unkn) unknown (My University, 2014)
In recent years the risks of emerging contaminants (ECs) have received substantial attention as potential environmental pollutants that persist in the environment due to their continual release. This research presents the work of three studies that provide critical insight into the spread of ECs, particularly antibiotic resistant bacteria derived from dairy manure and potentially harmful particles originated from nanomaterials in the soil-groundwater system. The adhesion of particles to mineral surfaces was quantified with the extended Derjaguin-Landau-Verwey-Overbeek (XDLVO) theory that includes Lifshitz-van der Waals, Lewis acid-base, electrostatic double layer and steric repulsion interactions. The transport of ECs was conducted in column transport experiments and the quartz sands served as the porous media. The first study specifically evaluated the effects of outer membrane protein (OMP) TolC on the transport of E.coli within saturated sands. The results showed that OMP TolC altered the surface tension components of E.coli cells which eventually led to higher mobility when the ionic strength was 20 mM or higher, suggesting that antibiotic resistant bacteria expressing OMP TolC could spread more widely within sandy aquifers. The second study evaluated the transport of manure-derived tetracycline resistant (tetR) and susceptible (tetS) E.coli in unsaturated porous media with specific focus on pore-water chemistry and moisture content. The experimental results showed that under both high and low soil moisture content terms, tetR E.coli displayed higher mobility than tetS E. coli under higher ionic strength conditions. An increase in soil moisture content from 0.12 to 0.23 as well as decrease in ionic strength of solution led to minimal release of previously retained E. coli cells. A transport model was fitted to the experimental results using the computer program HYDRUS-1D. The third study detailed deposition and remobilization of graphene oxide (GO) nanoparticles within saturated sands. The kinetics of GO was examined as a function of ionic strength and the remobilization of previously retained GO particles was investigated via chemical perturbation. The results revealed that deposition of GO particles on the surface of the quartz sands was highly dependent on ionic strength while the retention was limited by GO particles deposition capacities. The results of chemical perturbation suggested that GO particles could be remobilized in aqueous environment. The combined results from these three studies highlight the potential of ECs being spread in the soil-groundwater system and therefore pose serious public health risks.
Keywords: Antibiotic Resistant Bacteria; Bacterial Transport; Outer Membrane Proteins; Transport of Nanoparticles; Unsaturated Porous Media; XDLVO Theory